Now a Nobel gas: oxygen - Fandrey, Joachim; Schödel, Johannes; Eckardt, Kai-Uwe; Katschinski, Dörthe M.; Wenger, Roland H. (Pflügers Archiv: European Journal of Physiology, 2019)
The recent bestowal of the Nobel Prize 2019 in Physiology or Medicine to Gregg L. Semenza, Sir Peter J. Ratcliffe, and William G. Kaelin Jr. celebrates a series of remarkable discoveries that span from the physiological research question on how oxygen deficiency (hypoxia) induces the red blood cell forming hormone erythropoietin (Epo) to the first clinical application of a novel family of Epo-inducing drugs to treat patients suffering from renal anemia. This review looks back at the most important findings made by the three Nobel laureates, highlights current research trends, and sheds an eye on future perspectives of hypoxia research, including emerging and potential clinical applications.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Erythropoietin; High altitude; Hypoxia; Oxygen sensing; Protein hydroxylation; von Hippel-Lindau